PENGARUH STRES KERJA DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PENDIDIKAN KABUPATEN TORAJA UTARA - Melvipatricia Ampu Lembang; Jens Batara Marewa; Marinus Ronal (Smart Education, 2026)
This study aims to examine the effect of work stress and work culture on employee performance at the Education Office of North Toraja Regency. A quantitative research approach was employed using questionnaires and documentation for data collection. The study involved 46 employees, all of whom were selected as respondents through a census sampling technique. Data were analyzed using IBM SPSS with multiple linear regression, t-test, and F-test. The results revealed that work stress had no significant effect on employee performance, as indicated by a calculated t-value of -1.690, which was lower than the critical t-value of 2.016, with a significance level of 0.098 (>0.05). In contrast, work culture had a positive and significant effect on employee performance, with a calculated t-value of 5.525, exceeding the critical value of 2.016 and a significance level of 0.000 (<0.05). Simultaneously, work stress and work culture significantly influenced employee performance, as evidenced by an F-value of 19.563, which was greater than the F-table value of 3.21, with a significance level of 0.000 (<0.05). These findings indicate that work culture is the dominant factor in improving employee performance.